2020
DOI: 10.1111/bph.15076
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based discovery of CZL80, a caspase‐1 inhibitor with therapeutic potential for febrile seizures and later enhanced epileptogenic susceptibility

Abstract: Background and Purpose: Febrile seizures (FS), the most common seizures in childhood and often accompanied by later epileptogenesis, are not well controlled. Inflammatory processes have been implicated in the pathophysiology of epilepsy. However, whether caspase-1 is involved in FS generation and could be a target for the treatment of FS is still unclear. Experimental Approach: By using pharmacological and gene intervention methods in C57BL/6J mice, we assessed the role of caspase-1 in FS generation. We used s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Next, we asked whether pharmacological inhibition of caspase‐1 had a desirable effect on pharmacoresistant TLE. To answer this question, we tested the effect of CZL80, a structure‐based screened small‐molecular caspase‐1 inhibitor, on both pharmacoresistant TLE rats and mice 19 . In line with genetic ablation, intraperitoneal injection of CZL80 inhibited subicular pyramidal neuronal activities in vivo (Fig 5A), and dose‐dependently increased the ADTs of pharmacoresistant kindled rats; this effect was abolished by capase‐1 knockdown in the subiculum (Fig 5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we asked whether pharmacological inhibition of caspase‐1 had a desirable effect on pharmacoresistant TLE. To answer this question, we tested the effect of CZL80, a structure‐based screened small‐molecular caspase‐1 inhibitor, on both pharmacoresistant TLE rats and mice 19 . In line with genetic ablation, intraperitoneal injection of CZL80 inhibited subicular pyramidal neuronal activities in vivo (Fig 5A), and dose‐dependently increased the ADTs of pharmacoresistant kindled rats; this effect was abolished by capase‐1 knockdown in the subiculum (Fig 5B).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, female Wistar rats (250–300 g, grade II) with a stable rate of pharmacoresistance were selected according to previous studies 8,18 . Male caspase‐1 knockout ( Casp1 −/− ) and their wild‐type (WT) mice (25–30 g, grade II) on a C57BL/6J background were also used 19 . All animal care regimens and experiments were approved by the Animal Care and Use Committee of Zhejiang Chinese Medical University, and were in complete compliance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the inflammatory inhibitors may have potential antiepileptic effects. We previously reported that targeting the caspase-1-interleukin-1β inflammatory pathway could reduce neuronal excitability and suppress secondary epileptic susceptibility caused by febrile seizures ( 79 , 109 ). Besides, as mentioned above, the inhibitor of HMGB1 may also have the potential to treat secondary epileptogenesis ( 81 ).…”
Section: Available and Potential Treatments For Secondary Epileptogenesismentioning
confidence: 99%
“…The drug repurposing paradigm, which relies on finding new applications for “old” drugs [ 17 ], can guide the discovery of versatile anti-inflammatory agents where in silico methods could be essential to accelerate this process. However, despite the great potential of in silico methods such as molecular docking, quantitative structure–activity relationships (QSAR), tridimensional QSAR (3D-QSAR), pharmacophore modeling, molecular dynamics, and network pharmacology, they have only been applied to the search for inhibitors of either caspase-1 [ 18 , 19 , 20 , 21 , 22 ] or TNF-alpha [ 18 , 23 , 24 , 25 , 26 , 27 ], never both proteins. This demonstrates the limitations of these in silico methods, which are a reflection of the current’ single-target therapies to treat inflammation-based diseases.…”
Section: Introductionmentioning
confidence: 99%